Drivers of sustainable waste management in Asia - Agamuthu, Pariatamby; Hamid, F.S.; Khidzir, K.M. (2009)
Drivers of sustainable waste management are defined as groups of related factors that influence the development (or lack thereof) of industry. There has been no attempt to reasonably list the drivers that influence sustainable waste management in Asia. In this review, four groups of drivers of sustainable waste management, specifically of Asia, are explained. The four groups of drivers consist of three human elements (human, economic and institutional) and the environment as a single driving group. Typically, the first three groups have been very influential, with the environment driver, noticeably, only considered when preceded by other groups of drivers. The interconnectedness of the drivers and neglect of the environment driver is discussed. It is concluded that while the essence of the four groups of drivers can be found all over Asia, each driving group must be investigated in a local context and all information combined to devise sustainable waste management policies or strategies.